Philippine myths and legends : (values-oriented) - Aquino, Gaudencio V. (Mandaluyong City, 1992)
One constructive way of making use of our myths and legends is to make them available to our students. It is along this line of thinking that this volume has been written--as a textbook for high school students. To help carry out the purposes of classroom instruction, special effort was exerted to match vocabulary level with that of students in the secondary school.
Keywords: Legends- Philippines; Mythology- philippine